Intrapulmonary distribution of blood flow during exercise in pulmonary hypertension assessed by a new combination technique - Farina, Stefania; Pezzuto, Beatrice; Vignati, Carlo; Laveneziana, Pierantonio; Agostoni, Piergiuseppe (Frontiers in Cardiovascular Medicine, 2023)
Background. Hyperventilation and inadequate cardiac output (CO) increase are the main causes of exercise limitation in pulmonary hypertension (PH). Intrapulmonary blood flow partitioning between ventilated and not-ventilated lung zones is unknown. Thoracic impedance cardiography and inert gas rebreathing have been both validated in PH patients for non-invasive CO and pulmonary blood flow participating to gas exchange (PBF) measurements, respectively. This study sought to evaluate CO behaviour in PH patients during exercise and its partitioning between ventilated and not-ventilated lung areas, in parallel with ventilation partitioning between ventilated and not-ventilated lung zones. Methods. Eighteen PH patients (group 1 or 4) performed a cardiopulmonary exercise test (CPET) with a three-step loaded workload protocol. Steps were at 0%, 20%, 40% and 60% of peak workload reached during a preliminary maximum CPET. Ventilatory parameters, arterial blood gases, CO, PBF and intrapulmonary shunt (calculated as the differences between CO and PBF) were obtained at each step, combining thoracic impedance cardiography and inert gas rebreathing technique. Results. Dead space ventilation was throughout exercise ~40% of ventilation. A progressive increase of CO, from 4.86±1.24 l/min (rest) to 9.41±2.63 l/min (last step), PBF from 3.81±1.41 l/min to 7.21±2.93 l/min and intrapulmonary shunt from 1.05±0.96 l/min to 2.21±2.28 l/min was observed. Intrapulmonary shunt was ~20% of CO at each exercise step. Conclusions. Albeit the small population of the study, the combined non-invasive CO measurement seems a promising tool for deepening our knowledge of lung exercise hemodynamic in PH patients. This technique could be applied in future study to evaluate PH treatment influences on CO partitioning, being an increase of intrapulmonary shunt undesirable.